THE WEAKENING OF THE UNIVERSAL PROJECT OF MODERNITY IN THE CONTEXT OF GROWING MULTICULTURALISM, MIGRATION, AND RELIGIOUS DIVERSITY (Web of Teachers: Inderscience Research, 2025)
The article is devoted to an analysis of the weakening of the universal project of modernity, the growth of multiculturalism and migration, and the expansion of religious diversity. It examines key concepts that describe the weakening of the universal project of modernity and the expansion of religious diversity under the conditions of modernization, globalization, and cultural pluralism.